Repositioning Aspirin to Treat Lung and Breast Cancers and Overcome Acquired Resistance to Targeted Therapy - Li, Ling; Hu, Mengdi; Wang, Tao; Chen, Hongzhuan; Xu, Lu (Frontiers in Oncology, 2020)
Background: The major limitation of targeted cancer therapy is development of acquired resistance. Intratumoral heterogeneity and coexist of multiple resistance mechanisms make combination therapies targeting one specific mechanism inefficient. Methods: Transcriptional signature obtained from GEO was used to reposition FDA-approved drugs to treat lung and breast cancers as well as overcome acquired resistance to EGFR TKIs in lung cancer and to tamoxifen in breast cancer via CMap. In vitro and in vivo models were used to examine candidate drugs for their anti-cancer and anti-resistance efficacy and underlying mechanisms. Results: We find that aspirin, the most commonly used drug, not only inhibit proliferation and promote apoptosis of cancer cells, but also delay and overcome acquired resistance to targeted therapy using in vitro and in vivo models. The underlying mechanism could be attributed to enhanced cancer stemness and activated NF-kB signaling in acquired resistant tumors, both of which are suppressed by aspirin and render resistant tumors more sensitive to aspirin. Conclusions: Our data identify aspirin as a potential candidate for combination therapy for lung and breast cancers.